Solitary Plasmacytoma Involving Maxilla Treated by Multi-disciplinary Approach - Sadat, S M Anwar; Khan, Nuzhat; Fardaous, Jannatul; Golder, Krishna; Rita, Sufia Nasrin (Journal of Bangladesh College of Physicians and Surgeons, 2024)
Solitary plasmacytoma, a B-lymphocyte proliferating neoplastic rare entity can involve facial soft tissue and bone. The presenting case showed diffuse swelling in left mid face with maxillary bone destruction. The lesion was diagnosed as solitary plasmacytoma by conventional histopathology and immunohistochemistry. The case was successfully treated by multi-disciplinary approach with neo adjuvant radiotherapy followed by wide surgical excision without any relapse in three years follow up. J Bangladesh Coll Phys Surg 2024; 42: 199-203